The political projects and legal pluralism of institutions that address daily conflicts at the municipal level (Cuajinicuilapa, Guerrero, and Huejutla de Reyes, Hidalgo) - Esquivel Torres, Felipe de Jesús (2022)
The object of this research is to study the institutions that consider dialogue when dealing with the daily conflicts of citizens belonging to an ethnic group in the municipalities of Cuajinicuilapa, Guerrero, and Huejutla de Reyes, Hidalgo. The objective was to characterize the type of political project (authoritarian, neoliberal or participatory democratic) to which these institutions are ascribed, as well as the type of legal pluralism (conservative or emancipatory). The work is qualitative in nature, so information was collected through desk research, together with interviews with key actors in both communities. Among the findings, it was observed that the political projects of the institutions in charge of daily conflicts in both entities include features of both authoritarian and democratic projects. In terms of legal pluralism, the ambivalence between conservative and emancipatory is also observed.